IMPLEMENTASI PERATURAN MENTERI KELAUTAN DAN PERIKANAN NO. 2/PERMEN-KP/2015 TENTANG LARANGAN PENGGUNAAN ALAT PENANGKAPAN IKAN PUKAT HELA (TRAWLS) DAN PUKAT TARIK (SEINE NETS) TERHADAP USAHA PERIKANAN TANGKAP OLEH NELAYAN DI SIBOLGA - Sriayu Aritha Panggabean; Suhaidi Suhaidi; Jelly Leviza; Utari Maharany Barus (USU LAW JOURNAL, 2016)
ABSTRACT In accordance with the mandate of the Minister of Marine and Fisheries No. 2 / PERMEN-KP / 2015 on the Prohibition of the Use of Fish trawls and seine nets that the use of fishing gear trawls and seine nets in Regional Fisheries Management of the Republic of Indonesia has resulting in declining fish resources and threatening environmental sustainability of fish resources, but the implementation of the ministerial decree raises the pros and cons among fishermen in Indonesia, especially in Sibolga City. Therefore , this thesis seeks to analyze the regulation of the Minister of Marine and Fisheries No. 2 / PERMEN-KP / 2015 on the Prohibition of the Use of Fish trawls and seine nets the trawl fishery business by fishermen in Sibolga with a view of the aspects of the law itself and the destination aspects of the welfare state. Keywords : Fisherman , Business fisheries , Prohibition , Trawls , Seine Nets